GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 2624884 species occurrences available in GBIF matching the query: TaxonKey: Psittacidae. The dataset includes 2624884 records from 315 constituent datasets: 32 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 118 records from National Biodiversity Data Bank. Observation records, 1900-2014. 207 records from Ghent University - Zoology Museum - Vertebrate collection. 307 records from Plan de vertebrados de la Patagonia. 94 records from SUI Vertebrate Collection. 3 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 158522 records from OEH Atlas of NSW Wildlife. 16 records from CSUC Vertebrate Collection. 1 records from Aves de la cuenca media del río Bogotá. 11382 records from Australian National Wildlife Collection provider for OZCAM. 17 records from Aves de la cuenca media del río Chambery, Caldas. 1601 records from Coleção de Aves do Museu Nacional / UFRJ. 85 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 301 records from QLD DERM Coastal Bird Atlas (Trial). 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 2386 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 14 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 124 records from Zoology (Museum of Evolution - Uppsala). 17 records from CHAS Ornithology. 144 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 31 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 93 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 8 records from Perot Museum of Nature and Science. 2 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 2 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 198 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 113 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 356 records from Inventario Español de Especies Terrestres (MAGRAMA). 375 records from The avian collection at the Natural History Museum, Oslo, Norway. 14 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 3505 records from Southern African Bird Atlas Project. 8 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 3 records from UAFMC Birds. 436 records from DMNS Bird Collection (Arctos). 1 records from TTRS Ornithology. 13 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 66 records from University of Florida Vertebrate Paleontology. 35 records from ISM Ornithology Collection. 6 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 60 records from Colección Ornitológica de la Universidad Industrial de Santander. 48575 records from Fauna Atlas N.T.. 6624 records from Field Museum of Natural History (Zoology) Bird Collection. 156 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 26 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 2 records from HSU Wildlife Eggs and Nests. 16 records from Artdata. 7285 records from Museum Victoria provider for OZCAM. 5 records from Eggs Specimen. 25 records from CRCM Vertebrate Collection. 291 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 12 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 52194 records from SA Fauna (BDBSA). 9 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 4 records from MVZ Hildebrand Collection (Arctos). 40 records from Ornithologie ZMK. 333 records from Lund Museum of Zoology (MZLU). 3 records from Données ONF Faune-Flore-Fonge. 8 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 383 records from Bird Monitoring Data. 1 records from UCM Bird Eggs/Nests Collection (Arctos). 9 records from NCSM Birds Collection. 54318 records from Historical Bird Atlas. 70 records from UAM Bird Collection (Arctos). 8 records from CCBER Ornithology Collection. 705492 records from BirdLife Australia, Birdata. 4795 records from Museum of Comparative Zoology, Harvard University. 612 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 80 records from Censos navideños de aves y censo neotropical de aves acuáticas en 10 áreas protegidas de Parques Nacionales Naturales de Colombia.. 639 records from CAS Ornithology (ORN). 865083 records from EOD - eBird Observation Dataset. 404 records from Tasmanian Museum and Art Gallery provider for OZCAM. 151 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3614 records from iNaturalist Research-grade Observations. 451 records from Aranzadi Ringing Scheme (bird ring-recovery data). 30 records from NYSM Birds. 41 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 6 records from Birds collection of Abiko City Museum of Birds. 407 records from Birds collection of Yamashina Institute for Ornithology. 3 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 12 records from Musée Vert ornithology collection. 2 records from Alien Species in Poland - Animals. 18 records from Estonian Museum of Natural History. 10 records from University of California Museum of Paleontology. 1 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 1 records from KUBI Vertebrate Paleontology Collection. 7651 records from NMNH occurrence DwC-A. 7 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 23 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 1 records from Camiguin, Philippines Fauna. 12 records from Literature based species occurrence data of birds of North-East India. 1 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 1 records from Birdrace-Birding_for_Nature-Bonn. 15 records from MVZ Bird Observations (Arctos). 346 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 1 records from BIRDRACE Die Düsselmöwen. 99 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 1 records from BIRDRACE Bon(n)apartemöwen. 1 records from BIRDRACE Hügelland zu Fuß. 2 records from Tag der Artenvielfalt in Heidelberg. 1 records from Sürther Aue. 1 records from BIRDRACE Birding for Nature. 1 records from BIRDRACE Kingfisher. 3174 records from naturgucker. 10 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 20 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 33 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 11 records from BioGIS - Hamaarag. 1 records from Artenvielfalt im Rhein-Neckar-Raum. 57 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 95 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 165 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 19 records from Tissues Specimens. 2970 records from Museu Paraense Emilio Goeldi - Ornithology Collection - Skin. 93 records from Baillon Collection. 211201 records from First Bird Atlas. 64 records from SBMNH Vertebrate Zoology. 3 records from Bird Observation Data. 3 records from BioBlitz Barcelona 2010-14. 345 records from Northern Territory Museum and Art Gallery provider for OZCAM. 365 records from ICN - Universidad Nacional de Colombia. 38 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2007. 2717 records from LACM Vertebrate Collection. 33 records from Natural History Museum Rotterdam (NL) - Chordata collection. 32 records from Insecta ZMK. 1 records from BIRDRACE HGON Kelkheim-Rumpfteam. 19 records from Bird Collection of Yokosuka City Museum. 27 records from Collection Ornithologie - ZSRO. 11 records from Axel W. Erikssons African Birdcollection at Vänersborg Museum. 2973 records from Western Australian Museum provider for OZCAM. 1156 records from SysTax - Zoological Collections. 5682 records from Natural History Museum (London) Collection Specimens. 4125 records from Macaulay Library Audio and Video Collection. 243 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 7 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 10 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 28 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 14 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 1 records from Avifauna de la laguna Madre de Tamaulipas. 150 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 93 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 28 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 6 records from Inventario nacional de especies vegetales y animales de uso artesanal. 2 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 907 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 12 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 556 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 40 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 106 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 24 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 24 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 28 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 22 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 8 records from Ibaraki Nature Museum, Birds collection. 240 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 29 records from Collection Ornithologie - SNSD. 14 records from Collection Anatomie Histologie - SMF. 2133 records from Great Backyard Bird Count. 1 records from Ontario Breeding Bird Atlas 2001-2005. 17 records from Canadian Museum of Nature Bird Collection. 516 records from UWBM Ornithology Collection. 3 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 19 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 1 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1 records from Bird Collection of Otto Hedin. 45 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 16 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 13 records from Paleobiology Database. 2894 records from LSUMZ Birds Collection. 12 records from Bird collection of National Museum of Nature and Science. 431 records from Individual Sightings. 11 records from NBM birds. 147 records from Birds Specimens. 700 records from SDNHM Birds Collection. 120 records from IIAPPoa. 10 records from Bird Collection. 50 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 223 records from CNAV/Coleccion Nacional de Aves. 1 records from (UTCB) University of Tennessee - Birds Collection. 200 records from MMNH Museum Bird Collection. 1957 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 33 records from Biologiezentrum Linz. 83 records from Israel Nature and Parks Authority. 560 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 16 records from IndOBIS, Indian Ocean Node of OBIS. 363 records from UCLA Donald R. Dickey Bird and Mammal Collection. 3491 records from ORN. 452 records from Aves MZS. 1 records from Bird specimens in Gifu Prefectural Museum. 408 records from Aves laguna El Tinije. 83 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Chingaza. 6897 records from Naturalis Biodiversity Center (NL) - Aves. 1268 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 80 records from MZFC/Coleccion de Aves. 25 records from UCM Bird Collection (Arctos). 40 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 10 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 728 records from WFVZ Bird Collections. 441 records from Fundación Miguel Lillo - Colección Ornitológica. 1 records from Aves Bosque Seco Chicamocha. 111 records from Census of the threatened species of Benin. Data mobilized in the framework of BID REG project. 56 records from PSM Vertebrates Collection. 54 records from Natural History Museum, University of Tartu. 735 records from MLZ Bird Collection (Arctos). 10324 records from Southern African Bird Atlas Project 2: Full protocol records. 124 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 1142 records from Coleccion de sonidos ambientales. 8 records from DOF. 63 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 1 records from Vertebrate specimens of Jyväskylä University Museum. 1 records from Bird specimen detabase of Kanagawa Prefectural Museum of Natural History. 51 records from Biological and palaeontological collection and observation data MNHNL. 2559 records from Collection Aves (spirit preserved) SMF. 904 records from Collection Aves (bird skeletons) SMF. 2935 records from Collection Aves (bird skins) SMF. 36 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 119 records from UAZ Bird Collection. 19 records from DOF 2001-2006. 20077 records from AMNH Bird Collection. 18 records from Makira. 60 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 2037 records from DATAVES. 45 records from BioGIS - Birds - INPA database. 134 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 309 records from Ditsong National Museum of Natural History Collection: 1805-2008. 96 records from HSU Wildlife Birds. 272 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 7 records from MVZ Egg and Nest Collection (Arctos). 10 records from Ornitho.eus. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Guaminí (Carrique, octubre 1999). 396 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr).. 396 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from The reptiles, amphibians and fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 22 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 8 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 10 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 68 records from Códigos de barras de ADN del marcador COI de aves y tejidos de la colección del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt. 9 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 2296 records from Queensland Museum provider for OZCAM. 3459 records from CM Birds Collection. 290 records from ArtenFinder. 415 records from SuLaMa bird occurence data. 708 records from Auckland Museum Land Vertebrates Collection. 4 records from UWYMV Bird Collection (Arctos). 7 records from Caracterización de aves asociadas a los cultivos de flores de la Sabana de Bogotá y el Oriente Antioqueño. 14 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejo de Páramos Frontino-Urrao y Citará. 167 records from Geographically tagged INSDC sequences. 432 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 12 records from CMC_ornithology_GRC. 35 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 1 records from Norwegian Species Observation Service. 1020 records from SAFRING: Historical Bird Ringing Records (2005-2009). 28 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 127 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 128 records from rmca-albertine-rift-birds. 661 records from Animal Sound Archive. 1001 records from Bernice P. Bishop Museum. 2 records from National Invasive Species Database. 741 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 144 records from Cowan Tetrapod Collection - Birds. 2 records from Staffordshire Ecological Record - SER Species-based Surveys. 220 records from UTEP Vertebrates. 1 records from WNMU Bird Collection (Arctos). 2149 records from UMMZ Birds Collection. 77 records from Aves Collection of Institute of Systematics and Evolution of Animals. 1 records from European Molecular Biology Laboratory Australian Mirror. 786 records from DMNH Birds. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 1 records from DMNS Egg Collection (Arctos). 44 records from IICT Colecção Zoológica. 52 records from EBCC Atlas of European Breeding Birds. 163 records from MSB Bird Collection (Arctos). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Casilda (Luna & Piazza, octubre 1999). 1009 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 2 records from My naturesounds - nature observations with sound recordings. 343003 records from Garden Bird Surveys. 12 records from Inventario de Aves Mámbita. 372 records from Queen Victoria Museum Art Gallery provider for OZCAM. 4 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 3 records from Données ONF Faune-Flore-FOnge. 5 records from Observaciones de Especies Silvestres (by Charif Tala). 10 records from Caire-Chabrand Collection. 1 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta. 61 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 4295 records from Australian Museum provider for OZCAM. 61 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 355 records from Colección nacional de zoología. 10 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 144 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 898 records from MVZ Bird Collection (Arctos). 274 records from Occurrences in SinBIOTA. 1732 records from KUBI Ornithology Collection. 18 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 23 records from Anymals+plants - Citizen Science Data. 125 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 4 records from Colección Ornitológica Universidad de Nariño. 4 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 722 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 68 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 22 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 195 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 913 records from Data collected on scitizen science web portal www.ornitho.cat. 3 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 29 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 128 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 20 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 6 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 512 records from CUMV Bird Collection (Arctos). 5902 records from South Australian Museum Australia provider for OZCAM. 653 records from LSUMZ Bird Tissues. 10 records from ISU Birds. 7 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 2 records from 2011 Breeding Bird Survey of Taiwan. 593 records from Bird Collection of Museum and Institute of Zoology PAS. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences